Electronic exchanges the global transformation from pits to bits - Gorham, Michael
Anyone reading the business section of a newspaper lately knows that the financial exchanges--stock, bonds, FX, commodities, and so forth--are undergoing tremendous transformations. Fund managers, market makers, traders, exchange professionals, marekt data providers and analyzers, investors--anyone involved with the financial exchanges needs to understand the major forces pushing this transformation in order to position themselves and their institutions to the best advantage. In this book, veteran exchange expert Michael Gorham joins his twenty-five years of experience with CME and CBOT to the technical expertise of Nidhi Singh of Goldman Sachs to write a book that tells the story of this dramatic transformation. They chronicle the shift: --from floors to screens --from private clubs to public companies, and --from local and national to global competition. They analyze each of these shifts, identify the drivers behind them and look forward to the implications arising out of them for exchange business in the future. They also explore several key trends: --an increase in product innovation --the integration of markets from all over the world onto a single screen, --the rise of the modular exchange --the outsourcing of various exchange functions, and --the difficulty of transcending geography for regulatory purposes. So join Gorham and Singh in learning the story of this fundamental transformation. As old ways of working are being destroyed, entirely new types of jobs are being created, and new ways of working with exchanges. This book will help you chart the way forward to financial success.